Molecular Pathways That Involved in The Regulation of Some Cancer Initiating Cells: A Review (Iraqi Journal of Medical Sciences, 2023)
There are emerging data shows that different types of malignancies arising from cells called cancer initiating cells, which have self-renewal and tumorgenesity properties. Acquiring these properties make them able to initiate and transmit cancer. These cells are identified in different types of malignancies like stomach, colon, brain, breast and others. This review aims to identify the signaling pathways, which are involved in emerging these cells. Highly impact research papers regarding this subject were collected from trusted data base for analyzing. Analyzing these data identified that Notch, Hedgehog, high mobility group A2 (HMGA2), wingless/Int (Wnt)/B-catenin and epithelial mesenchymal transition (EMT) are the main signaling pathways, which are involved in this process. Targeting these signaling pathways will be a great technique to inhibit the formation of these cells. This will apply clinically as a treatment in different types of cancers and will be of great importance in treatment of cancers resisting chemotherapy.Keywords: Cancer stem cells (CSC), epithelial mesenchymal transition (EMT), chemotherapeutic, notch, hedgehogCitation: Mamoori AM, Farhood IG. Molecular pathways that involved in the regulation of some cancer initiating cells: A review. Iraqi JMS. 2023; 21(2): 166-171. doi: 10.22578/IJMS.21.2.3
Keywords: Cancer stem cells CSC; epithelial mesenchymal transition EMT; chemotherapeutic; notch; hedgehog